Case Report: Immune checkpoint inhibitor-related vitiligo-like depigmentation in non-melanoma advanced cancer: A report of three cases and a pooled analysis of individual patient data - Rao, Hui; Guo, Zheng; Wen, Xuejiao; Zeng, Xiaoli; Wu, Longqiu; Huang, Li (Frontiers in Oncology, 2023)
Background: Vitiligo-like depigmentation is a common skin adverse event in patients receiving immunotherapy for malignant melanoma, but has been rarely reported in patients with non-melanoma malignancies. To better understand this immune-related adverse event, we reviewed a series of cases of vitiligo-like depigmentation. Case presentation: We report three cases of vitiligo-like depigmentation after immune checkpoint inhibitor treatment in gastric adenocarcinoma, lung adenocarcinoma, and squamous cell carcinoma. The first case was treated with camrelizumab, the second was treated with QL1706 injection and sintilimab, and the third was treated with tislelizumab. Pembrolizumab, nivolumab, and ipilimumab caused the majority of vitiligo-like depigmentation, and all three of our patients experienced symptoms after taking other immune checkpoint inhibitors. Methods: Three patients who presented with vitiligo-like depigmentation after treatment with immune checkpoint inhibitors were selected. The clinical features, including radiological and histological examination, and the treatment process were reviewed. Eighteen previously published cases of vitiligo-like depigmentation were also used to analyze the results. The severity of vitiligo-like depigmentation in these cases was graded according to the Common Terminology Criteria for Adverse Events, version 5.0. Results: Vitiligo-like depigmentation occurred in 13 men (61.90%) and 8 women (38.10%), aged from 46 to 79 years, with an average age of 69.9 years. Of the 21 reviewed cases, vitiligo-like depigmentation was described in lung cancer (13/21, 61.90%), clear cell renal cell carcinoma (2/21, 9.52%), acute myeloid leukemia (1/21, 4.76%), cholangiocarcinoma (1/21, 4.76%), urothelial carcinoma (1/21, 4.76%), oral squamous cell carcinoma (1/21, 4.76%), esophageal squamous cell carcinoma (1/21, 4.76%), and gastric adenocarcinoma (1/21, 4.76%). The severity of vitiligo-like depigmentation after immunotherapy was unrelated to sex, age, cancer type, previous autoimmune diseases, and medication. Conclusions: Vitiligo-like depigmentation is a non-specific skin adverse event in melanoma immunotherapy,but arises as a direct result of treatment with immune checkpoint inhibitors. Vitiligo-like depigmentation has an irregular location, is not limited to direct sunlight cracks, and has also been reported on hair on the head, eyelashes, and eyebrows. People without any skin or autoimmune diseases can also experience vitiligo-like depigmentation after immunotherapy; the incidence of which is irrespective of sex, age, cancer type, previous autoimmune diseases, and medication.